Alunos autores no ensino médio: (re) educação linguoliterária na teoria holística da atividade e instrumentalização docente através da pesquisa-ação - Freitag, Felipe (2015)
The parameterization study of a didactic instrumental of interdependent teaching of Language and Literature for the High School of the Basic Education runs through the sensitization and literary authorship as pilots of guidelines in the construction of an affective motivation for the learning. Bazerman (2011) enhances that the teachers can and must consider more the social and cultural forms which surround the life of the students, as well as their affective lives, investing in their specific capacities of contextual management (cognitive and affective) with knowledge. For this purpose, the workshops of sensitization (awareness) to Literature, Reading and Textual Production, performed over the school semester in a second year class from the High School of the Basic Education, in a school of the state public education in the city of Santa Maria, Rio Grande do Sul, proposed themselves as a framework able to the development of didactic tools that articulated themselves, inside the interactionist approach, methodological procedures centralized in the so called sensitization processes, that is, techniques similar to the pre-activities inside a same interactionist paradigm. This founds itself in the precepts of the communicative teaching, at the same time that tries to establish a Zone of Proximal Development (VYGOTSKY, 2003) permeated of reflexive-critical practices capable of deflagrate an emergency of metacognitive insights. By the theoretical propositions of the Holistic Theory of Activity (RICHTER, 2006; 2008; 2010; 2011, 2015c), the factors of mediation oriented the activities elaborated under a procedural organogram, once that, the development of didactic tasks concentrated in aspects of scripting and, subsequently of authorship, organized themselves according to resources, strategies and concepts. These three groups are the subdivisions of the factors of THA (Holistic Theory of Activity) mediation. The resources, first mediation factor, are the material means (educative artifacts) with which dispose the professional and the client. The strategies, according to the mediation factor, are concrete operations of compatible objects with the cognitive targets to be reached by the professional at school. Therefore, the concepts, third mediation factor, consist in the knowledge that founds the procedures and the professional mediation. The sensitization workshops, proposed in this project, had as methodological basis in a procedural chart, greatly, the Research-action (THIOLLENT, 1996), in which, teachers and students are professional pairs in the personalization of proper investigation style of the real necessities of the students, during and after the learning, the Dialogism problem-solving Freirean (FREIRE; FAUDEZ, 1985), on what the dialogue is designed as action and reflection in the world and on what the are active subjects and collaborative knowledge construction, the Assimilation Theory of Mental Actions by Steps (GALPERIN, 1975), on what knowledge is by chain: motivation, verbalization, interaction and internalization and dialogic interacion (BAKHTIN, 2003) as dynamic appreciation of human demand practice ball.The parameterization of this formative instrumental of teachers founded itself in criteria of mapping of viable design to the proposal raised here as study focus, in view of the fact that, we give priority to a design of didactic material that would take into account the profile and the particularized necessities of the costumers, that is, which would value the expression of the subjects. The results obtained suggest the viability of the format of the course denominated Storyline, as far as its tangible achievements (production of narratives in chapters) originated, mainly, the construction of characters, whose identities are emulations of real processes of the students, that is, their projections as sociocultural subjects, by rivalry game methodology. This projection of socio-cultural subjects identities, more specifically, from adolescence of research subjects students is dependent to the rivalry game methodology, which intersects with Theories of Games (FIANI, 2004; HUIZINGA, 1971), with Theories of Adolescence (CALLIGARIS , 2014) and Theories of Psychology (KLEIN, 1973), so that the professional paradigmed decision-making are allocated on a teaching framework. The teaching framework of the Holistic Theory of Activity, through the didactic alliance and the inseparability of thinking, doing and feeling points to a reasoned methodological approach in the convergence between educational training and human development (cognition and affect) and know-how adviser development literary and linguistic teaching methods.